Subjek Profetik dalam Novel Orang-Orang Proyek Karya Ahmad Tohari - Andi Karman; Usman Usman; Muhammad Israq (Fakultas Sastra, Universitas Muslim Indonesia, 2026)
The phenomenon of corruption normalization in the digital era has triggered collective apathy and eroded human integrity amid corrupt bureaucratic practices, as portrayed by Ahmad Tohari in the novel Orang-Orang Proyek. This study aims to analyze how the novel reactualizes the prophetic function of literature in confronting bureaucratic pathology by employing the Prophetic Literature paradigm proposed by Kuntowijoyo. Using a qualitative descriptive method with a hermeneutic approach and content analysis techniques, this research examines the narrative of the character Kabul based on the three pillars of prophetic values: humanization, liberation, and transcendence. The findings reveal that the character Kabul represents a prophetic subject who successfully integrates professional expertise with moral-religious commitment. The aspect of humanization is reflected in Kabul’s efforts to protect the dignity of ordinary people from the dehumanizing practices within development projects. The aspect of liberation is manifested in his resistance to the “culture of tolerance” toward corruption and political pressure within the bureaucracy. Meanwhile, the aspect of transcendence appears in Kabul’s integrity, which frames his work as a spiritual mandate that transcends material interests. Therefore, this study affirms that the novel Orang-Orang Proyek functions not only as a representation of social reality but also as an instrument of social transformation and a medium of cultural dakwah that offers ethical solutions to the crisis of humanity and bureaucratic pathology in Indonesia.